2023
DOI: 10.1007/s00415-023-11561-0
|View full text |Cite
|
Sign up to set email alerts
|

MRI evidence of olfactory system alterations in patients with COVID-19 and neurological symptoms

Abstract: Background and objective Despite olfactory disorders being among the most common neurological complications of coronavirus disease 2019 (COVID-19), their pathogenesis has not been fully elucidated yet. Brain MR imaging is a consolidated method for evaluating olfactory system’s morphological modification, but a few quantitative studies have been published so far. The aim of the study was to provide MRI evidence of olfactory system alterations in patients with COVID-19 and neurological symptoms, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It may involve disrupting the olfactory system at different levels, from the sensory epithelium located in the olfactory clefts to olfactory neurons in the olfactory bulb and olfactory cortices ( Xydakis et al, 2021 ). Previous magnetic resonance imaging (MRI) studies revealed a variety of abnormalities of both peripheral and central olfactory areas, including olfactory cleft obstruction, abnormalities in olfactory bulb signal intensity and atrophy, and, notably, neurodegenerative changes in the limbic structures involved in the processing of olfactory stimuli and cognitive functions, also in patients with persistent OD ( Kandemirli et al, 2021 , Keshavarz et al, 2021 , Yildirim et al, 2022 , Douaud et al, 2022 , Capelli et al, 2023 ). Task-based olfactory functional MRI (fMRI) in COVID-19-related OD revealed absent activation of the orbitofrontal cortex and a more robust activation in the trigeminosensory activity ( Yildirim et al, 2022 , Ismail and Gad, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may involve disrupting the olfactory system at different levels, from the sensory epithelium located in the olfactory clefts to olfactory neurons in the olfactory bulb and olfactory cortices ( Xydakis et al, 2021 ). Previous magnetic resonance imaging (MRI) studies revealed a variety of abnormalities of both peripheral and central olfactory areas, including olfactory cleft obstruction, abnormalities in olfactory bulb signal intensity and atrophy, and, notably, neurodegenerative changes in the limbic structures involved in the processing of olfactory stimuli and cognitive functions, also in patients with persistent OD ( Kandemirli et al, 2021 , Keshavarz et al, 2021 , Yildirim et al, 2022 , Douaud et al, 2022 , Capelli et al, 2023 ). Task-based olfactory functional MRI (fMRI) in COVID-19-related OD revealed absent activation of the orbitofrontal cortex and a more robust activation in the trigeminosensory activity ( Yildirim et al, 2022 , Ismail and Gad, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the OS depth, no significant difference was found between the two groups for Yildirim et al [35]. Capelli et al [2] also showed significantly lower left, right, and total OBV in COVID-19 patients (196 patients of which 78 reported olfactory loss as the only neurological symptom) compared to 39 controls. They processed MRI images by ad hoc semi-automatic processing procedures.…”
Section: Obv and Os Depth Changesmentioning
confidence: 89%
“…Kandermirli et al [39] highlighted that 91.3% of cases with persistent COVID-19-related OD had abnormalities in the form of a diffusely increased OB signal intensity. Capelli et al [2] quantified, on 3D T2 FLAIR sequences, the OT median signal intensity, but no significant evidence was found in the COVID-19 patient group compared with control subjects, except for a few outliers. Li et al [44], in a case report, reported a 21-year-old male who had presented with a loss of smell for five days without any respiratory problems or fever and revealed hyperintensities inside bilateral olfactory nerves, suggestive of bilateral olfactory neuropathy beyond a smaller right OB.…”
Section: Obs Signal Intensitymentioning
confidence: 99%
See 2 more Smart Citations